BREAKING THE CHAIN OF STUNTING EARLY THROUGH MATERNAL HEALTH CARE BASED ON LOCAL COASTAL WISDOM KENDARI CITY : STUNTING - I Wayan Romantika; Narmi Narmi; Andi Nurhikma Mahdi; Ellyani Abadi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Stunting is a widespread health problem and needs to be a priority in achieving Indonesia's Golden Age. One cause is the low level of knowledge among pregnant women regarding the use of local foods. Therefore, it is necessary to break the chain of stunting early through education and regular health check-ups. Purpose: To determine the effect of local wisdom-based health assistance on knowledge, eating habits, and fetal heart rate (FHR) in pregnant women. Methods: The study used a quasi-experimental design with a two-group pre-post test. The sample consisted of 21 pregnant women in the coastal area of Kendari City, divided into 21 intervention groups and 21 control groups. The intervention provided was health assistance (education and regular health check-ups). The instruments used were questionnaires and fetal Doppler. Data were analyzed using the Mann-Whitney test. Results: Knowledge scores increased by an average of 15 before the intervention and 19 after the intervention. The control group's knowledge score before the intervention averaged 17 and 17 after the intervention. Eating habits in the intervention group averaged 289 before the intervention and 300 after the intervention. The control group's eating habits averaged 252 before the intervention and 264 after the intervention. Fetal heart rate in the intervention group increased from 133 before treatment to 143 after treatment. The control group's pre-test average was 137 and post-test average was 142. The Mann-Whitney test results showed a p-value of 0.000 <0.05 (knowledge), a p-value of 0.006 (eating habits), and a p-value of 0.004 (fetal heart rate). Conclusion: Local wisdom-based health assistance impacts knowledge and eating habits, as well as fetal heart rate.